2022
DOI: 10.3389/fncir.2022.978837
|View full text |Cite
|
Sign up to set email alerts
|

Axonal α7* nicotinic acetylcholine receptors modulate glutamatergic signaling and synaptic vesicle organization in ventral hippocampal projections

Abstract: Modulation of the release of glutamate by activation of presynaptic nicotinic acetylcholine receptors (nAChRs) is one of the most prevalent mechanism of nicotinic facilitation of glutamatergic transmission in cortico-limbic circuits. By imaging gene chimeric co-cultures from mouse, we examined the role of α7* nAChRs mediated cholinergic modulation of glutamate release and synaptic vesicle organization in ventral hippocampal projections. We directly visualized exogenous and endogenous cholinergic facilitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…α7nAChRs contribute to cognitive improvement during enhanced activation (Alvarez‐Jimenez et al., 2018; Bancroft & Levin, 2000; Esaki et al., 2021; Felix & Levin, 1997; Fukuda et al., 2019; Li et al., 2013; Lyon et al., 2012; Melichercik et al., 2012; Nott & Levin, 2006; Thomsen et al., 2010; Tian et al., 2015; Tinsley et al., 2011) and modulate transmitter release (Cheng & Yakel, 2014; Letsinger et al., 2022; Radcliffe & Dani, 1998; Zappettini et al., 2011; Zappettini et al., 2010; Zhong et al., 2022) by activating voltage gated Ca 2+ channels triggering Ca 2+ ‐mediated vesicular neurotransmitter release (Gray et al., 1996; Le Magueresse & Cherubini, 2007; Rathouz & Berg, 1994). Previous evidence has shown that moderate activation of α7nAChRs facilitates long‐term potentiation (LTP) induced by high‐frequency stimulation (Chen et al., 2016; Galvez et al., 2016; Hunter et al., 1994; Kroker et al., 2011; Nakauchi & Sumikawa, 2012), while relatively strong activation of α7nAChRs can induce LTP independently of high‐frequency stimulation (Mann & Greenfield, 2003; Ondrejcak et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α7nAChRs contribute to cognitive improvement during enhanced activation (Alvarez‐Jimenez et al., 2018; Bancroft & Levin, 2000; Esaki et al., 2021; Felix & Levin, 1997; Fukuda et al., 2019; Li et al., 2013; Lyon et al., 2012; Melichercik et al., 2012; Nott & Levin, 2006; Thomsen et al., 2010; Tian et al., 2015; Tinsley et al., 2011) and modulate transmitter release (Cheng & Yakel, 2014; Letsinger et al., 2022; Radcliffe & Dani, 1998; Zappettini et al., 2011; Zappettini et al., 2010; Zhong et al., 2022) by activating voltage gated Ca 2+ channels triggering Ca 2+ ‐mediated vesicular neurotransmitter release (Gray et al., 1996; Le Magueresse & Cherubini, 2007; Rathouz & Berg, 1994). Previous evidence has shown that moderate activation of α7nAChRs facilitates long‐term potentiation (LTP) induced by high‐frequency stimulation (Chen et al., 2016; Galvez et al., 2016; Hunter et al., 1994; Kroker et al., 2011; Nakauchi & Sumikawa, 2012), while relatively strong activation of α7nAChRs can induce LTP independently of high‐frequency stimulation (Mann & Greenfield, 2003; Ondrejcak et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The homopentameric α7 subunit‐containing subtype of nicotinic acetylcholine (ACh) receptors (α7nAChRs) is among the most common nicotinic receptor in the hippocampus (Alkondon & Albuquerque, 1993; Khiroug et al., 2003; Sudweeks & Yakel, 2000), present increased permeability to Ca 2+ (Albuquerque et al., 2009; Cheng et al., 2021; Khiroug et al., 2003). Although in the hippocampus α7nAChRs are predominately located on interneurons (Arnaiz‐Cot et al., 2008; Khiroug et al., 2003; Zappettini et al., 2011), they can also directly modulate pyramidal cells eliciting glutamate release (Cheng & Yakel, 2014; Letsinger et al., 2022; Radcliffe & Dani, 1998; Zappettini et al., 2010; Zhong et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…PNE has been shown to alter the expression and function of nAChRs across brain regions, leading to changes in presynaptic release and glutamatergic neurotransmission 4548 . Genetic deletion of α7 nAChRs decreases mEPSC frequency in the cortex and hippocampal neurons, indicating reduced number of glutamatergic synapses 49,50 . Additionally, PNE could impact presynaptic glutamate release through alterations in calcium signaling in the hippocampus and cortex 5153 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic deletion of α7 nAChRs decreases mEPSC frequency in the cortex and hippocampal neurons, indicating reduced number of glutamatergic synapses 49,50 .…”
Section: Effect Of Pne On Nachr Patterning and Glutamatergic Neurotra...mentioning
confidence: 99%
“…The expression of α7 nAChR is generally abundant in neuronal tissues, where it plays a crucial role in neurotransmitter transmission between neurons . Dysregulation of α7 nAChR has been implicated in neurodegenerative disorders, such as Alzheimer’s disease, causing impaired memory persistence and cognitive dysfunction. The nAChR family consists of various pentameric α and β subunits with a tissue-specific expression variation.…”
Section: Expression Of Nicotinic Acetylcholine Receptor (Nachr) In Lu...mentioning
confidence: 99%